Utilization of Gas from East Natuna Field for Improving Oil Recovery in Heavy and Light Oil Reservoir - Herdin Tandry, Renaldy
East Natuna Gas field is the largest undeveloped gas field in South East Asia because it has high CO2 content (71.21%). This huge CO2 content can be used to enhance oil recovery in the oil field by utilizing Natuna Gas as an injection fluid. This study was conducted by using commercial simulator software from CMG to simulate both heavy oil reservoir (API 20?) and light oil reservoir (API 37.4?) with Natuna gas injection to evaluate reservoir performance. There are four scenarios evaluated in this study: production simulation with natural flow, production simulation with Natuna gas injection, production simulation for 30 years period without water injection, followed by Natuna gas injection, production simulation with water injection in 30 years period, followed by Natuna gas injection in 20 years after. The natural flow scenario gives oil recovery around 23.6 percent in light oil reservoir while gives 25.6 percent recovery in heavy oil reservoir. For the three other scenarios, light oil reservoir gives higher additional recovery than heavy oil reservoir which gives oil recovery around 65.9 – 70.5 percent in light oil reservoir and 57.6 – 66.1 percent in heavy oil reservoir. In general, Natuna gas injection gives a good performance in oil recovery for both heavy oil and light oil reservoir. In addition, the presence of waterflood does not give any significant result in total oil recovered when the reservoir was injected with Natuna Gas. The highest oil recovery for both heavy oil (66.1%) and light oil reservoir (70.5%) can be obtained by injecting Natuna gas from the beginning of the production phase. Furthermore, Natuna gas performed better in light oil reservoir compared to heavy oil reservoir. This study gives new development scenario that can utilize gas from East Natuna field for improving oil recovery in both light and heavy oil reservoir near East Natuna Field and helps to fulfill Indonesia energy needs in the future.